CHEMICAL QUALITY OF CONCENTRATE BISCUIT CONTAINED FORAGE WITH DIFFERENT STORAGE PERIOD - ., WAHYUNI; DIANITA, RAHMI; MUTHALIB, R. A.; ., AFZALANI (Majalah Ilmiah Peternakan; Vol 26 No 1 (2023): Vol. 26 No. 1 (2023), 2023)
Storage period is one of the factors which affect the physical and chemical quality of the stored material. This study aimed to determine the effect of storage period on the chemical quality of livestock concentrate biscuits con- taining Indigofera and sengon. Four periods of storage period were arranged in a completely randomized design which was repeated 5 times. The storage period consisted of 0, 7, 14 and 21 days. The chemical qualities observed in- cluded moisture and ash content, crude protein and crude fiber. The results showed that storage period significantly reduced the moisture content of concentrate biscuit, while the ash content, crude protein and crude fiber were not affected by storage period. It was concluded that the concentrate biscuits containing Indigofera and sengon could be stored for up to 21 days with good chemical quality.